The Extermination of Animals and Men: On Tadeusz Śliwiak’s Poemat o miejskiej rzeźni - Niesporek, Katarzyna (Porównania, 2021)
The aim of the article is an interpretation of Tadeusz Śliwiak’s Poemat o miejskiej rzeźni. Śliwiak puts equal signs between the slaughterhouse and the concentration camp, and between the suffering of Jews and farm animals with which he enters the modern discussion on these matters. The poet, trying to understand “the first law of wolf ” and “the last law of man”, realizes that there are no boundaries between “human” and “animal”; that one should accept the animalistic part of human existence. In the perspective of war, death and extermination, everyone suffers likewise.